Structural, thermal and microstructural studies of the proton conductor BaCe0.7Zr0.1Y0.05Zn0.15O3 for IT-SOFCs. Issue 1 (March 2016) - Hossain, S; Radenahmad, N; Zaini, J H; Begum, F; Azad, A K
Abstract: The specimen of BaCe0.7 Zr0.1 Y0.05 Zn0.15 O3, a perovskite-type electrolyte, has been synthesized for application in an anode-supported protonic solid oxide fuel cell by the conventional solid state reaction in air at 1200°C for 12 hours. Structural and thermal characterization has been performed using room temperature X-ray diffraction (XRD), Scanning Electron Microscopy (SEM), Thermogravimetric Analysis (TGA) and Differential Thermal Analysis (DTA). Rietveld analysis of the XRD data has been analyzed by FullProf program and confirmed the single phase of the sample with an orthorhombic crystal structure in the Pbnm space group. To understand the temperature dependent behaviour TG/DTA scan of the precursor was recorded. The TG/DTA scan was performed under constant flow of Argon which exhibits a gradual weight loss up to 900 o C. The SEM image of the pellet surface of the sample shows that the sample sintered at 1200 o C was dense and suitable to use as electrolyte in solid oxide fuel cells (SOFCs).